Aqueous iron ion battery and preparation method thereof
By using Na3V2(PO4)3/C as the positive electrode material and elemental iron powder as the negative electrode material in the aqueous iron ion battery, the problems of positive electrode material capacity and negative electrode material stability are solved, and battery performance with high capacity, long life and cycle stability are achieved.
Patent Information
- Application Number
- CN202411704116.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-04-04
AI Technical Summary
Currently, water-based iron ion batteries lack high capacity and long-life materials in the positive electrode materials, and there are hydrogen evolution and dendrite problems in the negative electrode materials, resulting in poor circulation stability.
Na3V2(PO4)3/C is used as the positive electrode active material and prepared by liquid phase ball milling-low temperature sintering method to obtain a material with a micron-scale nanosheet structure and a high specific surface area. At the same time, elemental iron powder is used as the negative electrode material and prepared by roll forming technology to avoid dendrites and improve hydrogen evolution reaction.
The high capacity and long life of the aqueous iron ion battery are achieved, the preparation process of the positive electrode material is simple, the circulation stability of the negative electrode material is greatly improved, and the battery is easy to assemble and low cost.
Smart Images

Figure CN119764605A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to an aqueous iron ion battery and a preparation method thereof. Background Art
[0002] As my country vigorously develops sustainable energy, battery energy storage technology has also received widespread attention and rapid development. As one of the most common energy storage technologies, lithium-ion batteries are widely used in portable electronic devices and electric vehicles. However, the shortage of lithium resources has led to the high price of lithium materials, and the flammability of organic electrolytes has limited its development in the field of large-scale energy storage in the future. Therefore, in recent years, researchers have gradually turned their attention to aqueous multivalent batteries (such as zinc ion batteries, magnesium ion batteries, calcium ion batteries, iron ion batteries, etc.) that are lower in cost, easier to assemble, and safer. Compared with batteries with single electron transfer, systems using multivalent ions can achieve higher storage capacity and energy density due to multiple electron transfers involved in redox reactions.
[0003] Among many alternative materials, iron metal stands out due to its abundant resources and low price. Aqueous iron-ion batteries have several significant advantages over traditional lithium-ion batteries. First, iron is the fourth most abundant element in the earth's crust, with reserves far higher than lithium and costs far less than lithium; second, aqueous iron-ion batteries use water as a solvent as electrolyte, avoiding the flammable and explosive risks of organic electrolytes in traditional lithium batteries, and have higher safety; more importantly, the metallic iron negative electrode has a high theoretical specific capacity of 960 mA h / g and a higher redox potential (-0.44V relative to the standard hydrogen electrode), which means that the iron metal negative electrode is more stable in aqueous electrolytes and is not prone to dendrites, thereby greatly improving the cycle stability of aqueous iron ions. Because it does not contain active metals, aqueous iron-ion batteries do not produce toxic gases or environmental pollutants during production and assembly, making them a green and environmentally friendly energy storage technology.
[0004] However, the current research on aqueous iron-ion batteries is still in its initial stage. 2+ The high polarization of the anode limits its diffusion kinetics, making it lack of high-capacity and long-life cathode materials; on the other hand, the hydrogen evolution problem and dendrite problem of the metal anode lead to its poor cycle stability. Based on this, it is of great significance to develop an aqueous iron ion battery with high capacity and long life. Summary of the invention
[0005] In view of the above deficiencies in the prior art, the present invention provides an aqueous iron ion battery with high capacity and long life and a preparation method thereof.
[0006] To achieve the above purpose, the specific technical solutions of the present invention are as follows:
[0007] An aqueous iron ion battery comprises a positive electrode and a negative electrode; wherein the positive electrode is made of raw materials including Na3V2(PO4)3 / C; and the negative electrode is made of raw materials including elemental iron powder.
[0008] Preferably, the elemental iron powder includes but is not limited to at least one of pig iron powder, reduced iron powder, carbonyl iron powder, nano iron powder, electrolytic iron powder, and atomized iron powder.
[0009] Preferably, the preparation method of Na3V2(PO4)3 / C comprises the following steps:
[0010] S1, adding organic sodium salt, vanadium source and phosphorus source into ball milling solvent to obtain a mixed solution;
[0011] S2, ball-milling the mixed solution to a particle size of 100 nm~10 μm to obtain a precursor dispersion;
[0012] S3, drying the precursor dispersion to obtain a precursor powder;
[0013] S4. Sinter the precursor powder under an inert atmosphere to obtain the positive electrode active material Na3V2(PO4)3 / C.
[0014] The aqueous iron ion battery of the present invention uses Na3V2(PO4)3 / C as the positive electrode active material, uses organic sodium salt as both the sodium source and the carbon source, and is prepared by a simple liquid phase ball milling-low temperature sintering method. The production and preparation process is simple. The prepared Na3V2(PO4)3 / C has a nanosheet structure of micron size, with a size in the range of 2 to 20 µm. This structure significantly increases the specific surface area of the material (74.5459 m 2 / g), further shortening the diffusion distance of iron ions and effectively preventing the material from pulverizing and expanding in volume; at the same time, the larger specific surface area provides more active sites for electrochemical reactions, thereby improving the electrochemical performance of aqueous iron-ion batteries.
[0015] Preferably, the ball milling time is 10 to 48 h.
[0016] Preferably, the ball milling solvent is at least one of deionized water, methanol, ethanol, propanol and isopropanol.
[0017] Preferably, the organic sodium salt is Na3C6H5O7, NaC2H3O2, Na2C4O4, Na2C4H4O4, NaHCO2, C6H 11 NaO7、C6H 11At least one of NaO6, NaC4H4O5, Na2C4H4O6, C7H5NaO2, and C2H4NNaO2.
[0018] Preferably, the vanadium source is at least one of V2O5, V2O3, VO2, V2O4, NH4VO3, and VCl3.
[0019] Preferably, the phosphorus source is at least one of (NH4)3PO4, NH4H2PO4, Na2HPO4, (NH4)2HPO4, NaH2PO4, and H3PO4.
[0020] Preferably, the drying temperature is 60-150° C., and the drying time is 6-24 h.
[0021] Preferably, the sintering temperature is 550-900° C., and the sintering time is 5-25 h.
[0022] Preferably, the aqueous iron ion battery also includes an electrolyte.
[0023] Preferably, the electrolyte is an aqueous solution of Fe(CF3SO3)2, and the concentration of the aqueous solution of Fe(CF3SO3)2 is 1~5 mol / L.
[0024] The present invention also provides a method for preparing the aqueous iron ion battery, comprising the following steps:
[0025] (1) Mix Na3V2(PO4)3 / C, acetylene black and polyvinylidene fluoride, add an appropriate amount of 1-methyl-2-pyrrolidone and grind evenly to obtain a positive electrode slurry. Apply the positive electrode slurry on carbon paper with a surface density of 1.0-2.0 mg / cm 2 , drying to obtain a positive electrode sheet;
[0026] (2) Mixing elemental iron powder, carbon source, and binder in proportion to obtain a mixed slurry, pressing the mixed slurry into a sheet, and drying to obtain a negative electrode sheet;
[0027] (3) The positive electrode sheet, glass fiber membrane, and negative electrode sheet are placed in order, electrolyte is added, and the opening is sealed to obtain an aqueous iron ion battery.
[0028] Preferably, the mass ratio of Na3V2(PO4)3 / C, acetylene black and polyvinylidene fluoride is 8:1:1.
[0029] Preferably, the carbon source is at least one of single-walled carbon nanotubes, acetylene black, Super P, graphite, nanocarbon fibers, graphene oxide, multi-walled carbon nanotubes, Ketjen black, and organic carbon.
[0030] Preferably, the binder is at least one of PTFE (polytetrafluoroethylene), PAA (polyacrylic acid), PEO (polyethylene oxide), LA133 (acrylonitrile multipolymer), CMC (carboxymethyl cellulose), PVDF (polyvinylidene fluoride), and SBR (styrene-butadiene rubber).
[0031] Preferably, the mass ratio of the elemental iron powder, the carbon source and the binder is (5-8): (2-4): (1-3).
[0032] Preferably, the thickness of the pressed sheet is 10-50 μm.
[0033] Compared with the prior art, the present invention is beneficial in that:
[0034] (1) The aqueous iron ion battery provided by the present invention has the advantages of high capacity and long life. Specifically, at a current density of 100 mA / g, it has a discharge specific capacity of 171.2 mA h / g, and at a current density of 500 mA / g, after 7000 cycles, its capacity retention rate is as high as 91.9%.
[0035] (2) The positive electrode active material Na3V2(PO4)3 / C of the aqueous iron ion battery of the present invention is prepared by a simple liquid phase ball milling-low temperature sintering method. The production process is simple. The prepared Na3V2(PO4)3 / C has a nanosheet structure of micrometer size, with a size in the range of 2 to 20 µm. This structure significantly increases the specific surface area of the material (74.5459 m 2 / g), further shortening the diffusion distance of iron ions and effectively preventing the material from pulverizing and expanding in volume; at the same time, the larger specific surface area provides more active sites for electrochemical reactions, thereby improving the electrochemical performance of aqueous iron-ion batteries.
[0036] (3) The positive electrode material Na3V2(PO4)3 / C of the aqueous iron ion battery of the present invention selects organic sodium salt as the sodium source. The organic sodium salt can provide the required sodium source for the reaction. During low-temperature sintering, the organic components in the organic sodium salt decompose in situ to form a carbon coating layer, which further improves the electronic conductivity of the material, thereby improving the electrochemical activity.
[0037] (4) The negative electrode of the aqueous iron ion battery of the present invention is prepared by a simple roll-forming technology, and its preparation process is simple and the product consistency is good. Compared with the traditional metal negative electrode, the negative electrode of the present invention exhibits the advantages of no dendrite generation and greatly improved hydrogen evolution reaction, thereby further improving the cycle stability of the aqueous iron ion battery; at the same time, the presence of the carbon source also further improves the electronic conductivity of the negative electrode material.
[0038] (5) The positive and negative electrode materials of the aqueous iron ion battery of the present invention are abundant in resources and low in cost. In addition, the battery is easy to assemble (it can be assembled in the air), which conforms to the characteristics of green chemistry and is conducive to market promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is the XRD pattern of the sodium vanadium phosphate positive electrode material prepared in Example 1;
[0040] Figure 2 XRD pattern of the negative electrode sheet prepared in Example 1;
[0041] Figure 3 This is a SEM image of the sodium vanadium phosphate positive electrode material prepared in Example 1;
[0042] Figure 4 This is a SEM image of the negative electrode sheet prepared in Example 1;
[0043] Figure 5 The aqueous iron ion battery of Example 1 is at 100 mA·g -1 Charge and discharge curves under current density;
[0044] Figure 6 The aqueous iron ion battery of Example 1 is at 500 mA·g -1 Battery cycling performance at different current densities. DETAILED DESCRIPTION
[0045] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] The present invention provides an aqueous iron ion battery, comprising a positive electrode and a negative electrode; wherein the positive electrode is made of raw materials including Na3V2(PO4)3 / C; and the negative electrode is made of raw materials including elemental iron powder.
[0047] In some examples, the elemental iron powder includes, but is not limited to, at least one of pig iron powder, reduced iron powder, carbonyl iron powder, nano iron powder, electrolytic iron powder, and atomized iron powder.
[0048] The preparation method of Na3V2(PO4)3 / C comprises the following steps:
[0049] S1, adding organic sodium salt, vanadium source and phosphorus source into ball milling solvent to obtain a mixed solution;
[0050] S2, ball-milling the mixed solution to a particle size of 100 nm~10 μm to obtain a precursor dispersion;
[0051] S3, drying the precursor dispersion to obtain a precursor powder;
[0052] S4. Sinter the precursor powder under an inert atmosphere to obtain the positive electrode active material Na3V2(PO4)3 / C.
[0053] In some examples, the ball milling time is 10 to 48 h.
[0054] In some examples, the ball milling solvent is at least one of deionized water, methanol, ethanol, propanol, and isopropanol.
[0055] In some examples, the organic sodium salt is Na3C6H5O7, NaC2H3O2, Na2C4O4, Na2C4H4O4, NaHCO2, C6H 11 NaO7、C6H 11 At least one of NaO6, NaC4H4O5, Na2C4H4O6, C7H5NaO2, and C2H4NNaO2; the vanadium source is at least one of V2O5, V2O3, VO2, V2O4, NH4VO3, and VCl3; the phosphorus source is at least one of (NH4)3PO4, NH4H2PO4, Na2HPO4, (NH4)2HPO4, NaH2PO4, and H3PO4.
[0056] In some examples, the drying temperature is 60-150° C., and the drying time is 6-24 h.
[0057] In some examples, the sintering temperature is 550-900° C., and the sintering time is 5-25 h.
[0058] The preparation method of the aqueous iron ion battery comprises the following steps:
[0059] (1) Mix Na3V2(PO4)3 / C, acetylene black and polyvinylidene fluoride, add an appropriate amount of 1-methyl-2-pyrrolidone and grind evenly to obtain a positive electrode slurry. Apply the positive electrode slurry on carbon paper with a surface density of 1.0-2.0 mg / cm 2 , drying to obtain a positive electrode sheet;
[0060] (2) Mixing elemental iron powder, carbon source, and binder in proportion to obtain a mixed slurry, pressing the mixed slurry into a sheet, and drying to obtain a negative electrode sheet;
[0061] (3) The positive electrode sheet, glass fiber membrane, and negative electrode sheet are placed in order, electrolyte is added, and the opening is sealed to obtain an aqueous iron ion battery.
[0062] In some examples, the carbon source is at least one of single-walled carbon nanotubes, acetylene black, Super P, graphite, nanocarbon fiber, graphene oxide, multi-walled carbon nanotubes, Ketjen black, and organic carbon.
[0063] In some examples, the binder is at least one of PTFE, PAA, PEO, LA133, CMC, PVDF, and SBR.
[0064] In some examples, the mass ratio of the elemental iron powder, carbon source, and binder is (5-8): (2-4): (1-3).
[0065] In some examples, the pressed sheet has a thickness of 10-50 μm.
[0066] Example 1
[0067] Aqueous iron ion battery
[0068] Preparation of positive electrode active material:
[0069] S1. Weigh Na3C6H5O7, V2O5, and NH4H2PO4 in a molar ratio of 3:2:3 and add them into a mixed solvent of methanol and deionized water (the volume ratio of methanol to water is 2:1) to obtain a mixed solution A;
[0070] S2, adding the mixed solution A into the ball mill, and ball milling for 24 h until a precursor dispersion with a suspended particle size of 100 nm~10 μm is obtained;
[0071] S3, drying the precursor dispersion at 120 °C for 12 h to obtain a precursor powder;
[0072] S4. The precursor powder was sintered at 800 °C under nitrogen atmosphere for 10 h, cooled to room temperature, and then sieved to obtain the positive electrode material Na3V2(PO4)3 / C.
[0073] Preparation of aqueous iron ion batteries:
[0074] (1) Na3V2(PO4)3 / C, acetylene black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, and an appropriate amount of 1-methyl-2-pyrrolidone was added and then ground evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on carbon paper with a surface density of 1.0-2.0 mg / cm 2 , and then placed in an oven at 120 °C for 12 h and cut into circular electrode sheets with a diameter of 10 mm;
[0075] (2) Reduced iron powder, carbon nanotube slurry, and PTFE emulsion were mixed in a mass ratio of 6:3:2 to obtain a mixed slurry, and the mixed slurry was placed in a roller press to be pressed into a sheet with a thickness of 20 μm; then, the sheet was dried in an oven at 120 °C for 12 h, and cut into circular electrode sheets with a diameter of 12 mm;
[0076] (3) An aqueous iron ion battery was assembled in air using CR2025 stainless steel as the battery casing, 3 mol / L Fe(CF3SO3)2 aqueous solution as the electrolyte, and a glass fiber membrane as the separator. The positive electrode, glass fiber membrane, and negative electrode were placed in this order, and the electrolyte was added and the battery was sealed to obtain an aqueous iron ion battery.
[0077] Figure 1 The X-ray diffraction pattern of the Na3V2(PO4)3 / C positive electrode material prepared in this example. It can be seen from the XRD pattern that the obtained Na3V2(PO4)3 is consistent with the standard spectrum. Figure 1 The product is consistent without any impurity peaks and has good crystallinity.
[0078] Figure 2 This is the X-ray diffraction pattern of the negative electrode sheet prepared in this embodiment. It can be seen from the XRD pattern that the diffraction peak of the obtained Fe / C composite is consistent with that of elemental Fe. At the same time, the presence of carbon can also be seen, and no impurity peaks appear.
[0079] Figure 3 This is the SEM image of the Na3V2(PO4)3 / C cathode material prepared in this example. It can be seen from the figure that the obtained Na3V2(PO4)3 / C is a nanosheet structure with a size in the range of 2~20 µm.
[0080] Figure 4 This is a SEM image of the negative electrode sheet prepared in this embodiment. It can be seen from the figure that its surface is smooth and flat.
[0081] Example 2
[0082] Aqueous iron ion battery
[0083] Preparation of positive electrode active material:
[0084] S1. Weigh Na2C4O4, V2O3, and NH4H2PO4 in a molar ratio of 3:2:3 and add them into deionized water to obtain a mixed solution A;
[0085] S2, adding the mixed solution A into the ball mill and ball milling for 12 h to obtain a precursor dispersion with a suspended particle size of 100 nm~10 μm;
[0086] S3, drying the precursor dispersion at 60 °C for 18 h to obtain a precursor powder;
[0087] S4. The precursor powder was sintered at 825 °C under nitrogen atmosphere for 8 h. After cooling to room temperature, the positive electrode material Na3V2(PO4)3 / C was obtained by sieving.
[0088] Preparation of aqueous iron ion batteries:
[0089] (1) Na3V2(PO4)3 / C, acetylene black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, and an appropriate amount of 1-methyl-2-pyrrolidone was added and then ground evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on carbon paper with a surface density of 1.0-2.0 mg / cm 2 , and then placed in an oven at 120 °C for 12 h and cut into circular electrode sheets with a diameter of 10 mm;
[0090] (2) Carbonyl iron powder, Super P slurry and PTFE emulsion were mixed in a mass ratio of 7:2:1 to obtain a mixed slurry, and the mixed slurry was placed in a roller press to be pressed into a sheet with a thickness of 20 μm; then, the sheet was placed in an oven at 120°C and dried for 12 h, and cut into circular electrode sheets with a diameter of 12 mm;
[0091] (3) An aqueous iron ion battery was assembled in air using CR2025 stainless steel as the battery casing, 3 mol / L Fe(CF3SO3)2 aqueous solution as the electrolyte, and a glass fiber membrane as the separator. The positive electrode, glass fiber membrane, and negative electrode were placed in this order, and the electrolyte was added and the battery was sealed to obtain an aqueous iron ion battery.
[0092] Example 3
[0093] Aqueous iron ion battery
[0094] Preparation of positive electrode active material:
[0095] S1, weigh C6H according to the molar ratio of 3:2:3 11 NaO7, NH4VO3, and H3PO4 are added to methanol to obtain a mixed solution A;
[0096] S2, adding the mixed solution A into the ball mill and ball milling for 16 h to obtain a precursor dispersion with a suspended particle size of 100 nm~10 μm;
[0097] S3, drying the precursor dispersion at 100 °C for 10 h to obtain a precursor powder;
[0098] S4. The precursor powder was sintered at 750 °C under nitrogen atmosphere for 12 h, cooled to room temperature, and then sieved to obtain the positive electrode material Na3V2(PO4)3 / C.
[0099] Preparation of aqueous iron ion batteries:
[0100] (1) Na3V2(PO4)3 / C, acetylene black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, and an appropriate amount of 1-methyl-2-pyrrolidone was added and then ground evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on carbon paper with a surface density of 1.0-2.0 mg / cm 2 , and then placed in an oven at 120 °C for 12 h and cut into circular electrode sheets with a diameter of 10 mm;
[0101] (2) Pig iron powder, single-walled carbon nanotube slurry, and PVDF emulsion were mixed in a mass ratio of 7:2:1 to obtain a mixed slurry, and the mixed slurry was placed in a roller press to be pressed into a sheet with a thickness of 20 μm; then, the sheet was placed in an oven at 120 °C and dried for 12 h, and cut into circular electrode sheets with a diameter of 12 mm;
[0102] (3) An aqueous iron ion battery was assembled in air using CR2025 stainless steel as the battery casing, 3 mol / L Fe(CF3SO3)2 aqueous solution as the electrolyte, and a glass fiber membrane as the separator. The positive electrode, glass fiber membrane, and negative electrode were placed in this order, and the electrolyte was added and the battery was sealed to obtain an aqueous iron ion battery.
[0103] Comparative Example 1
[0104] Aqueous iron ion battery
[0105] Preparation of positive electrode active material:
[0106] S1. Weigh NaOH, VO2, and (NH4)3PO4 in a molar ratio of 3:2:3 and add them into a mixed solvent of methanol and deionized water (the volume ratio of methanol to water is 2:1) to obtain a mixed solution A;
[0107] S2, adding the mixed solution A into the ball mill, and ball milling for 24 h until a precursor dispersion with a suspended particle size of 100 nm~10 μm is obtained;
[0108] S3, drying the precursor dispersion at 120 °C for 12 h to obtain a precursor powder;
[0109] S4. Sinter the precursor powder at 800 °C under nitrogen atmosphere for 10 h, cool to room temperature, and then sieve to obtain the positive electrode material Na3V2(PO4)3.
[0110] Preparation of aqueous iron ion batteries:
[0111] (1) Na3V2(PO4)3, acetylene black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, and an appropriate amount of 1-methyl-2-pyrrolidone was added and then ground evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on carbon paper with a surface density of 1.0-2.0 mg / cm 2 , and then placed in an oven at 120 °C for 12 h and cut into circular electrode sheets with a diameter of 10 mm;
[0112] (2) Reduced iron powder, carbon nanotube slurry, and PTFE emulsion were mixed in a mass ratio of 6:3:2 to obtain a mixed slurry, and the mixed slurry was placed in a roller press to be pressed into a sheet with a thickness of 20 μm; then, the sheet was dried in an oven at 120 °C for 12 h, and cut into circular electrode sheets with a diameter of 12 mm;
[0113] (3) An aqueous iron ion battery was assembled in air using CR2025 stainless steel as the battery casing, 3 mol / L Fe(CF3SO3)2 aqueous solution as the electrolyte, and a glass fiber membrane as the separator. The positive electrode, glass fiber membrane, and negative electrode were placed in this order, and the electrolyte was added and the battery was sealed to obtain an aqueous iron ion battery.
[0114] Comparative Example 2
[0115] Aqueous iron ion battery
[0116] Preparation of positive electrode active material:
[0117] S1. Weigh NaCl, V2O4, and NH4H2PO4 in a molar ratio of 3:2:3 and add them into a mixed solvent of methanol and deionized water (the volume ratio of methanol to water is 2:1) to obtain a mixed solution A;
[0118] S2, adding the mixed solution A into the ball mill, and ball milling for 24 h until a precursor dispersion with a suspended particle size of 100 nm~10 μm is obtained;
[0119] S3, drying the precursor dispersion at 120 °C for 12 h to obtain a precursor powder;
[0120] S4. Sinter the precursor powder at 800 °C under nitrogen atmosphere for 10 h, cool to room temperature, and then sieve to obtain the positive electrode material Na3V2(PO4)3.
[0121] Preparation of aqueous iron ion batteries:
[0122] (1) Na3V2(PO4)3, acetylene black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, and an appropriate amount of 1-methyl-2-pyrrolidone was added and then ground evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on carbon paper with a surface density of 1.0-2.0 mg / cm2 , and then placed in an oven at 120 °C for 12 h and cut into circular electrode sheets with a diameter of 10 mm;
[0123] (2) Reduced iron powder, carbon nanotube slurry, and PTFE emulsion were mixed in a mass ratio of 6:3:2 to obtain a mixed slurry, and the mixed slurry was placed in a roller press to be pressed into a sheet with a thickness of 20 μm; then, the sheet was dried in an oven at 120 °C for 12 h, and cut into circular electrode sheets with a diameter of 12 mm;
[0124] (3) An aqueous iron ion battery was assembled in air using CR2025 stainless steel as the battery casing, 3 mol / L Fe(CF3SO3)2 aqueous solution as the electrolyte, and a glass fiber membrane as the separator. The positive electrode, glass fiber membrane, and negative electrode were placed in this order, and the electrolyte was added and the battery was sealed to obtain an aqueous iron ion battery.
[0125] Comparative Example 3
[0126] Aqueous iron ion battery
[0127] Preparation of positive electrode active material:
[0128] S1. Weigh Na2CO3, VCl3, (NH4)3PO4 in a molar ratio of 3:2:3, and add them into a mixed solvent of methanol and deionized water (the volume ratio of methanol to water is 2:1) to obtain a mixed solution A;
[0129] S2, adding the mixed solution A into the ball mill, and ball milling for 24 h until a precursor dispersion with a suspended particle size of 100 nm~10 μm is obtained;
[0130] S3, drying the precursor dispersion at 120 °C for 12 h to obtain a precursor powder;
[0131] S4. Sinter the precursor powder at 800 °C under nitrogen atmosphere for 10 h, cool to room temperature, and then sieve to obtain the positive electrode material Na3V2(PO4)3.
[0132] Preparation of aqueous iron ion batteries:
[0133] (1) Na3V2(PO4)3, acetylene black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, and an appropriate amount of 1-methyl-2-pyrrolidone was added and then ground evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on carbon paper with a surface density of 1.0-2.0 mg / cm 2 , and then placed in an oven at 120 °C for 12 h and cut into circular electrode sheets with a diameter of 10 mm;
[0134] (2) Reduced iron powder, carbon nanotube slurry, and PTFE emulsion were mixed in a mass ratio of 6:3:2 to obtain a mixed slurry, and the mixed slurry was placed in a roller press to be pressed into a sheet with a thickness of 20 μm; then, the sheet was dried in an oven at 120 °C for 12 h, and cut into circular electrode sheets with a diameter of 12 mm;
[0135] (3) An aqueous iron ion battery was assembled in air using CR2025 stainless steel as the battery casing, 3 mol / L Fe(CF3SO3)2 aqueous solution as the electrolyte, and a glass fiber membrane as the separator. The positive electrode, glass fiber membrane, and negative electrode were placed in this order, and the electrolyte was added and the battery was sealed to obtain an aqueous iron ion battery.
[0136] Comparative Example 4
[0137] Aqueous iron ion battery
[0138] The Na3V2(PO4)3 / C prepared in Example 1 is used as the positive electrode active material, and the preparation method of the aqueous iron ion battery is as follows:
[0139] (1) Na3V2(PO4)3 / C, acetylene black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, and an appropriate amount of 1-methyl-2-pyrrolidone was added and then ground evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on carbon paper with a surface density of 1.0-2.0 mg / cm 2 , and then placed in an oven at 120 °C for 12 h and cut into circular electrode sheets with a diameter of 10 mm;
[0140] (2) Cut the 20 μm thick iron sheet into a circular electrode sheet with a diameter of 12 mm;
[0141] (3) An aqueous iron ion battery was assembled in air using CR2025 stainless steel as the battery casing, 3 mol / L Fe(CF3SO3)2 aqueous solution as the electrolyte, and a glass fiber membrane as the separator. The positive electrode, glass fiber membrane, and negative electrode were placed in this order, and the electrolyte was added and the battery was sealed to obtain an aqueous iron ion battery.
[0142] Comparative Example 5
[0143] Aqueous iron ion battery
[0144] The Na3V2(PO4)3 / C prepared in Example 2 is used as the positive electrode active material, and the preparation method of the aqueous iron ion battery is as follows:
[0145] (1) Na3V2(PO4)3 / C, acetylene black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, and an appropriate amount of 1-methyl-2-pyrrolidone was added and then ground evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on carbon paper with a surface density of 1.0-2.0 mg / cm 2 , and then placed in an oven at 120 °C for 12 h and cut into circular electrode sheets with a diameter of 10 mm;
[0146] (2) Cut the 20 μm thick iron sheet into a circular electrode sheet with a diameter of 12 mm;
[0147] (3) An aqueous iron ion battery was assembled in air using CR2025 stainless steel as the battery casing, 3 mol / L Fe(CF3SO3)2 aqueous solution as the electrolyte, and a glass fiber membrane as the separator. The positive electrode, glass fiber membrane, and negative electrode were placed in this order, and the electrolyte was added and the battery was sealed to obtain an aqueous iron ion battery.
[0148] Comparative Example 6
[0149] Aqueous iron ion battery
[0150] The Na3V2(PO4)3 / C prepared in Example 3 is used as the positive electrode active material, and the preparation method of the aqueous iron ion battery is as follows:
[0151] (1) Na3V2(PO4)3 / C, acetylene black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, and an appropriate amount of 1-methyl-2-pyrrolidone was added and then ground evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on carbon paper with a surface density of 1.0-2.0 mg / cm 2 , and then placed in an oven at 120 °C for 12 h and cut into circular electrode sheets with a diameter of 10 mm;
[0152] (2) Cut the 20 μm thick iron sheet into a circular electrode sheet with a diameter of 12 mm;
[0153] (3) An aqueous iron ion battery was assembled in air using CR2025 stainless steel as the battery casing, 3 mol / L Fe(CF3SO3)2 aqueous solution as the electrolyte, and a glass fiber membrane as the separator. The positive electrode, glass fiber membrane, and negative electrode were placed in this order, and the electrolyte was added and the battery was sealed to obtain an aqueous iron ion battery.
[0154] Comparative Example 7
[0155] Aqueous iron ion battery
[0156] Preparation of positive electrode active material:
[0157] S1. Weigh NaCl, V2O5, and NH4H2PO4 in a molar ratio of 3:2:3 and add them to a mixed solvent of methanol and deionized water (the volume ratio of methanol to water is 2:1), and add citric acid, the mass of which is 30% of the total mass of NaCl, V2O5, and NH4H2PO4, to obtain a mixed solution A;
[0158] S2, adding the mixed solution A into the ball mill, and ball milling for 24 h until a precursor dispersion with a suspended particle size of 100 nm~10 μm is obtained;
[0159] S3, drying the precursor dispersion at 120 °C for 12 h to obtain a precursor powder;
[0160] S4. The precursor powder was sintered at 800 °C under nitrogen atmosphere for 10 h, cooled to room temperature, and then sieved to obtain the positive electrode material Na3V2(PO4)3 / C.
[0161] Preparation of aqueous iron ion batteries:
[0162] (1) Na3V2(PO4)3 / C, acetylene black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, and an appropriate amount of 1-methyl-2-pyrrolidone was added and then ground evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on carbon paper with a surface density of 1.0-2.0 mg / cm 2 , and then placed in an oven at 120 °C for 12 h and cut into circular electrode sheets with a diameter of 10 mm;
[0163] (2) Reduced iron powder, carbon nanotube slurry, and PTFE emulsion were mixed in a mass ratio of 6:3:2 to obtain a mixed slurry, and the mixed slurry was placed in a roller press to be pressed into a sheet with a thickness of 20 μm; then, the sheet was dried in an oven at 120 °C for 12 h, and cut into circular electrode sheets with a diameter of 12 mm;
[0164] (3) An aqueous iron ion battery was assembled in air using CR2025 stainless steel as the battery casing, 3 mol / L Fe(CF3SO3)2 aqueous solution as the electrolyte, and a glass fiber membrane as the separator. The positive electrode, glass fiber membrane, and negative electrode were placed in this order, and the electrolyte was added and the battery was sealed to obtain an aqueous iron ion battery.
[0165] The electrochemical performance of the aqueous iron ion batteries prepared in Examples 1 to 3 and Comparative Examples 1 to 7 was tested using a BlueDian CT2001A battery testing system. Figures 5 and 6 And Table 1.
[0166] Figure 5 The aqueous iron ion battery prepared in Example 1 is -1The charge and discharge curve under current density. It can be seen from the figure that the discharge specific capacity of the aqueous iron ion battery in the 0-1 V charge and discharge range is 171.2 mA h / g.
[0167] Figure 6 The aqueous iron ion battery prepared in Example 1 was charged and discharged in the range of 0-1V, 500 mA·g -1 Cycling performance diagram under current density. As can be seen from the figure, the aqueous iron ion battery has excellent cycle stability, and its capacity retention rate is as high as 91.9%, with the advantages of high capacity and long life.
[0168] Table 1: Performance test results of aqueous iron ion batteries prepared in Examples 1 to 3 and Comparative Examples 1 to 7
[0169]
[0170] It can be seen from Table 1 that the aqueous iron ion battery prepared by the present invention has a -1 The discharge capacity at the current density can reach 171.2 mA h / g. -1 At the current density of 100 mA·g, the capacity retention rate after 7000 cycles is as high as 91.9%; the aqueous iron ion battery (Comparative Examples 1-3) using inorganic sodium salt as the sodium source to prepare the positive electrode material Na3V2(PO4)3 has a lower discharge specific capacity and poor cycle performance; the aqueous iron ion battery (Comparative Examples 4-6) using metal iron sheet as the negative electrode has a lower discharge specific capacity and poor cycle performance at 100 mA·g -1 It has a higher discharge specific capacity under current density, but its cycle performance is worse than that of the aqueous iron ion battery of the present invention; an aqueous iron ion battery (Comparative Example 7) in which the positive electrode material Na3V2(PO4)3 / C is prepared by adding an external carbon source has a discharge specific capacity equivalent to that of the aqueous iron ion battery of the present invention, but its cycle performance is worse than that of the aqueous iron ion battery of the present invention.
[0171] In summary, the aqueous iron ion battery provided by the present invention uses Na3V2(PO4)3 / C as the positive electrode active material and single iron powder as the main negative electrode active material; wherein, the Na3V2(PO4)3 / C is prepared by specific raw materials and methods, and has a nanosheet structure of micrometer size, which can promote the improvement of the electrochemical performance of the battery; the negative electrode of the aqueous iron ion battery of the present invention, compared with the traditional metal negative electrode, shows the advantages of no dendrite generation and greatly improved hydrogen evolution reaction, which can further improve the cycle stability of the battery. The aqueous iron ion battery provided by the present invention has the advantages of high capacity and long life; in addition, the positive and negative electrode materials of the battery are abundant in resources and low in cost, and the battery is easy to assemble, which conforms to the characteristics of green chemistry and is conducive to market promotion.
[0172] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. An aqueous iron ion battery, characterized in that: It includes a positive electrode and a negative electrode; wherein the positive electrode is made of raw materials including Na3V2(PO4)3 / C; and the negative electrode is made of raw materials including elemental iron powder.
2. An aqueous iron ion battery according to claim 1, characterized in that: The elemental iron powder includes but is not limited to at least one of pig iron powder, reduced iron powder, carbonyl iron powder, nano iron powder, electrolytic iron powder, and atomized iron powder.
3. An aqueous iron ion battery according to claim 1, characterized in that: The preparation method of Na3V2(PO4)3 / C comprises the following steps: S1, adding organic sodium salt, vanadium source and phosphorus source into ball milling solvent to obtain a mixed solution; S2, ball-milling the mixed solution to a particle size of 100 nm~10 μm to obtain a precursor dispersion; S3, drying the precursor dispersion to obtain a precursor powder; S4. Sinter the precursor powder under an inert atmosphere to obtain the positive electrode active material Na3V2(PO4)3 / C.
4. An aqueous iron ion battery according to claim 3, characterized in that: The organic sodium salt is Na3C6H5O7, NaC2H3O2, Na2C4O4, Na2C4H4O4, NaHCO2, C6H 11 NaO7、C6H 11 At least one of NaO6, NaC4H4O5, Na2C4H4O6, C7H5NaO2, and C2H4NNaO2; the vanadium source is at least one of V2O5, V2O3, VO2, V2O4, NH4VO3, and VCl3; the phosphorus source is at least one of (NH4)3PO4, NH4H2PO4, Na2HPO4, (NH4)2HPO4, NaH2PO4, and H3PO4.
5. An aqueous iron ion battery according to claim 3, characterized in that: The sintering temperature is 550-900°C, and the sintering time is 5-25 h.
6. The aqueous iron ion battery according to claim 1, characterized in that: It also includes an electrolyte, which is an aqueous solution of Fe(CF3SO3)2.
7. A method for preparing an aqueous iron ion battery, characterized in that: The following steps are involved: (1) Na3V2(PO4)3 / C, acetylene black and polyvinylidene fluoride are mixed, and an appropriate amount of 1-methyl-2-pyrrolidone is added and then ground evenly to obtain a positive electrode slurry, and the positive electrode slurry is coated on carbon paper and dried to obtain a positive electrode sheet; (2) Mixing elemental iron powder, carbon source, and binder in proportion to obtain a mixed slurry, pressing the mixed slurry into a sheet, and drying to obtain a negative electrode sheet; (3) The positive electrode sheet, glass fiber membrane, and negative electrode sheet are placed in order, electrolyte is added, and the opening is sealed to obtain an aqueous iron ion battery.
8. The method for preparing an aqueous iron ion battery according to claim 7, characterized in that: The mass ratio of Na3V2(PO4)3 / C, acetylene black and polyvinylidene fluoride is 8:1:
1.
9. The method for preparing an aqueous iron ion battery according to claim 7, characterized in that: The carbon source is at least one of single-walled carbon nanotubes, acetylene black, Super P, graphite, nanocarbon fibers, graphene oxide, multi-walled carbon nanotubes, Ketjen black, and organic carbon.
10. The method for preparing an aqueous iron ion battery according to claim 7, characterized in that: The mass ratio of the elemental iron powder, carbon source and binder is (5-8): (2-4): (1-3).